Structure and mechanical performance for TiAlN films that are grown with a low Al composition - Hua Huang; Chun-Sheng Chen; Chih-Chung Hu; Lian-Wang Lee; Chun-Yao Hsu (Materials Research Express, 2020)
An orthogonal array L _9 (3 ^4 ) is used with the grey Taguchi design to optimize the performance of TiAlN films that are grown by direct current magnetron co-sputtering, using a low Al concentration. The structure, mechanical performance and the cutting properties of a coated TiAlN tool for which the films are deposited using various parameters are determined. For the optimal deposition conditions, the (111) diffraction peak intensity increases, which demonstrates an improvement in the crystallinity of the TiAlN films. A TiAlN film coated cutter insert is used for the dry milling of a Cr-Mo alloy steel workpiece and it is shown that the tool flank wear decreases and there are fewer surface defects proved. In the confirmation cutting tests the surface roughness is decreased by 26.08% and the flank wear is 16.15% less. The TiAlN films exhibit good mechanical performance, using grey relational analysis, the improvement rate in hardness H is 14.74%, in friction coefficient is 45.88%, in elastic modulus E is 9.56%, in H/E is 9.09% and in H ^3 /E ^2 is 25.92%.